An examination of the associations between the locations of probationers and crimes: A city block-level analysis - Titus, Stephanie A. (2004)
This research will use adult probation data from the Douglas County Court Probation Office for 2000 and 2001 to evaluate the relationship between the locations of probationers and their possible effects on the amount of crime on residential city blocks in Omaha, Nebraska. The analyses will relate the probation data to the dependent variables that are based on the Part I Index Crimes obtained from the Omaha Police Department. The research will attempt to evaluate the effects of probationers on the amount of crime on city blocks and compare this with the effects of block-level characteristics and crime on the locations of probationers. This comparison involves using strategies related to Granger Causality to assess whether the presence of probationers leads to crime rather than high crime areas becoming areas where probationers live. Matrix Exponential Spatial Specification (MESS) regression will also be used to evaluate these effects because this technique permits adjusting for spatial autocorrelation which could be important when dealing with very small unit of analysis such as city blocks